Characterization of the pH signal transduction pathway gene palA of Aspergillus nidulans and identification of possible homologs. - Negrete-Urtasun, S (1997)
We have cloned the palA gene of Aspergillus nidulans, one of six genes participating in ambient pH signal transduction in a regulatory circuit mediating pH regulation of gene expression. The derived 798-residue PalA protein is 29.4% identical over its entire length to a hypothetical protein from the nematode Caenorhabditis elegans and also has possible yeast homologs.